Tree thieves : crime and survival in North America's woods - Bourgon, Lyndsie (Little, Brown Spark, 2022)
Weaving together investigative reporting, colorful characters, logging history, political analysis, and cutting-edge tree science, this gripping account reveals the complexity of the illegal timber market.